Need analysis and the role of engagement of commercial fitness centers in Malaysia - Ong, Derek Lai Teik * (Global Alliance of Marketing & Management Associations, 2014)
Commercial fitness industry is booming in Malaysia and is becoming more difficult to entice new members with the built up competition. This research investigates the needs of these commercial fitness members and the role of engagement in determining overall satisfaction with service. Scale of Service Quality for Recreational Sport (SSQRS) was used for data collection reveals that fitness members are more drawn to interaction, outcome, physical environment quality and the engagement they receive from a gym membership and not much from the programs that are offered. This study’s finding will contribute to the development of marketing strategies for the sustainable growth of the fitness industry.